Development and characterization of new contrast agents for Photon-Counting CT - Donabauer, Mika; Sawall, Stefan; Ayx, Isabelle; Wängler, Carmen; Schönberg, Stefan; Wängler, Björn (European journal of radiology, 2026)
Purpose - The development of novel contrast agents is a critical step in unleashing the full potential of Photon-Counting Computed Tomography (PCCT), as clinically approved iodine contrast agents do not exhibit optimal spectral properties to harness the full potential of photon-counting detectors. Moreover, material decomposition requires the application of different contrast agents with differing X-ray attenuation characteristics at different photon energies. However, the development of contrast agents being suitable for this purpose is in its infancy, limiting the imaging options of PCCT. In this study, we investigated which of the elements lanthanum, gadolinium, ytterbium, lead, bismuth and gold are suitable for use as the basis of contrast agents in PCCT as these should exhibit highly interesting X-ray attenuation characteristics at different tube voltages for this application. - Methods - New contrast agents based on the aforementioned elements were synthesized and characterized in terms of stability. Further, these substances were characterized by phantom studies on the first FDA-approved clinical PCCT Naeotom Alpha scanner with regard to contrast generation at different tube voltages of 70, 90, 120, and 140 kV in comparison to the approved iodine-based contrast agent Gastrolux to determine their general potential for PCCT imaging. - Results - We found that at lower tube voltages of 70 kV, iodine (48.1 ± 0.8 HU/(mg/mL)) and gadolinium (43.5 ± 1.0 HU/(mg/mL)) demonstrated the highest attenuation rates, whereas lanthanum, gold, ytterbium, and lead showed lower X-ray attenuation efficiency under these conditions (35.7 ± 0.7, 28.1 ± 0.6, 25.8 ± 0.2, and 25.3 ± 0.1 HU/(mg/mL), respectively). At a higher tube voltage of 120 kV, the situation changed, showing the highest attenuation rates for gadolinium, ytterbium, and iodine (33.4 ± 0.4, 28.1 ± 0.1, and 24.6 ± 0.3 HU/(mg/mL), respectively), followed by gold, bismuth, lanthanum, and lead (23.5 ± 0.3, 21.7 ± 0.2, 19.7 ± 0.3, and 18.1 ± 0.1 HU/(mg/mL), respectively). - Conclusions - Although all elements investigated showed a general suitability for implementation in contrast-enhanced CT imaging, iodine, gadolinium and ytterbium demonstrated the highest potential in this regard. However, also gold and bismuth could in general be suitable for material decomposition studies in combination with the aforementioned elements in cases necessitating a strongly varying contrasting behavior at chosen tube voltages.
Online verfügbar: 31. Dezember 2025, Artikelversion: 2. Januar 2026
Gesehen am 19.02.2026